Super enhancers as key drivers of gene regulatory networks in normal and malignant hematopoiesis - Cheng, Ying; Pei, Guangxin; Zhang, Hengchao; Hou, Yan; Sun, Lei; Xu, Hongdi; Lv, Yuning; Wu, Xiuyun (Frontiers in Cell and Developmental Biology, 2025)
Super enhancers (SEs) are clusters of enhancers with exceptionally high transcriptional activity, crucial for determining cell identity and regulating gene expression. They function as key regulatory hubs, governing gene networks essential for normal hematopoiesis while also driving the pathogenesis of hematological malignancies. This review summarizes the role of SEs in maintaining hematopoietic lineage identity and examines how their dysregulation in acute myeloid leukemia (AML), myelodysplastic neoplasms (MDS), adult T-cell leukemia (ATL), acute lymphoblastic leukemia (ALL), and multiple myeloma (MM) leads to oncogenic activation. By regulating key oncogenes, SEs represent promising therapeutic targets. Emerging strategies-such as BET inhibitors, CDK7/9 inhibitors, and rational drug combinations-effectively disrupt SE-driven transcriptional programs and show potential to overcome treatment resistance in these cancers.